Identification and frequency analysis of drought–flood abrupt alternation events using a daily-scale standardized weighted average of the precipitation index - Zhou, Wan; Liu, Dedi; Zhang, Jiayu; Jiang, Sainan; Xing, Shuying; Wang, Junde; Cheng, Yufei; Chen, Nana (Frontiers in Environmental Science, 2023)
Drought-flood abrupt alternation (DFAA), which is defined as the rapid transition between drought and flood in a short term, amplifies the negative impacts of individual drought or flood. DFAA is divided into drought to flood (DTF) and flood to drought (FTD) according to the sequences of drought and flood. Previous studies of identifying DFAA events are mostly conducted on a long timescale (e.g., over a month), leading to inaccurate identifications or omissions of DFAA events. Besides, frequency analysis of DTF and FTD events, which is vital for design of hydraulic structures and water supply systems, is rarely studied. This study establishes an identification method for DFAA events based on a daily-scale standardized weighted average of precipitation index (SWAP) and conducts frequency analysis of DTF and FTD events based on copula theory. The Han River Basin (HRB), China, a very crucial area for water resources management, is selected as the study area. Our findings disclose that: DFAA events happen less frequently with larger intensities and durations during 1961 to 2020. The temporal trends of DTF and FTD events vary with similar trends while numbers of DTF events are less than that of FTD events, indicating that FTD is the main performance of DFAA in HRB. Besides, the identification processes of DFAA events at Wuhan station are analyzed in detail, which proves SWAP to be an effective index to capture the change of precipitation and accurately depict the occurrences of droughts and floods. Furthermore, drought intensity (DI) and flood intensity (FI) are selected for bivariate frequency analysis. OR case is defined as DI≥di or FI≥fi while AND case is defined as DI≥di and FI≥fi. The results of frequency analysis show that the joint return periods (JRPs) of DFAA events under OR case are basically equal in three sub-basins, meaning similar occurrence probability of drought-flood disaster. JRPs under AND case are increasing from upper, middle to lower basin as a whole, indicating the decreasing risk of suffering from abrupt drought-flood transitions. Overall, this study may have potential value in the early warning and mitigation of DFAA disaster.